2012
DOI: 10.5194/bgd-9-15501-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Groundwater and porewater as a major source of alkalinity to a fringing coral reef lagoon (Muri Lagoon, Cook Islands)

Abstract: To better predict how ocean acidification will affect coral reefs, it is important to understand how biogeochemical cycles on reefs alter carbonate chemistry over various temporal and spatial scales. This study quantifies the contribution of fresh groundwater discharge (as traced by radon) and shallow porewater exchange (as quantified from advective chamber incubations) to total alkalinity (TA) dynamics on a fringing coral reef lagoon along the southern Pacific island of Rarotonga over a tidal and diel cycle. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…S1-S2). Prior studies have found elevated TA in SGD 15,28 and it has been hypothesized that this elevated TA may help buffer coral reefs from low pH waters in the SGD and possibly even from ocean acidification 28,38,39 . Conversely, at the low alkalinity site (Cabral), there was no relationship between pH and NEC (Fig.…”
Section: Cascading Impacts Of Sgd On Community Calcification Via Meta...mentioning
confidence: 99%
See 2 more Smart Citations
“…S1-S2). Prior studies have found elevated TA in SGD 15,28 and it has been hypothesized that this elevated TA may help buffer coral reefs from low pH waters in the SGD and possibly even from ocean acidification 28,38,39 . Conversely, at the low alkalinity site (Cabral), there was no relationship between pH and NEC (Fig.…”
Section: Cascading Impacts Of Sgd On Community Calcification Via Meta...mentioning
confidence: 99%
“…Submarine groundwater discharge (SGD) is a natural land-sea connection that is found worldwide 25,26 and is a template to explore how allochthonous inputs affect interactions between biological and geochemical processes. SGD has a complex mixture of components and is a major source of new solutes that can influence coastal salinity, carbonate dynamics, nutrient fluxes, and the composition and concentration of dissolved organic matter [27][28][29] . SGDdriven solutes have been linked to changes in algal species richness 30,31 , coral and macroalgal growth 32,33 , bioerosion 32,34 , and net ecosystem production and calcification 15,35 on coral reefs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation